Factors Influencing Fertile Age Couples in the Use of Long-Term Contraceptive Methods (MKJP) - Batubara, Novita Sari; Batubara, Rini Amalia; Siregar, Rya Anastasya (International Journal of Public Health Excellence (IJPHE), 2025)
The success of the National Family Planning (KB) Movement in encouraging increased community participation in building increasingly independent small families must be considered and even improved because this achievement is not evenly distributed. Likewise, what happened in the Patiluban Mudik Health Center work area where the number of Fertile Age Couples using KB was only a portion of the total number of Fertile Age Couples recorded up to May 2023, which was 514 PUS. The purpose of the study was to determine the factors that influence fertile age couples in terms of the use of Long-Term Contraceptive Methods (MKJP) in the Patiliuban Mudik Health Center Work Area, Natal District, Mandailing Natal Regency in 2023. The research method is quantitative research with a cross-sectional study design approach. The study was conducted in the working area of ​​Patiluban Mudik Health Center with a sample size of 92 people. The analysis used was Chi Square. The results showed a significant relationship between knowledge and the use of MKJP (P value = 0.018 <0.05), there was a significant relationship between family support and the use of MKJP (P value = 0.0033 > 0.05). There was a relationship between parity and the use of MKJP (P value = 0.011 <0.05), The results of this study recommend that Patiluban Mudik Health Center be more intensive in providing counseling about MKJP so that the number of KB users, especially MKJP, can be increased and to find factors that influence PUS not to be willing to use the MKJP method.